Extended Combined Neonatal Treatment With Erythropoietin Plus Melatonin Prevents Posthemorrhagic Hydrocephalus of Prematurity in Rats - Robinson, Shenandoah; Conteh, Fatu S.; Oppong, Akosua Y.; Yellowhair, Tracylyn R.; Newville, Jessie C.; Demerdash, Nagat El; Shrock, Christine L.; Maxwell, Jessie R.; Jett, Stephen; Northington, Frances J.; Jantzie, Lauren L. (Frontiers in Cellular Neuroscience, 2018)
Posthemorrhagic hydrocephalus of prematurity (PHHP) remains a global challenge. Early preterm infants (<32 weeks gestation), particularly those exposed to chorioamnionitis (CAM), are prone to intraventricular hemorrhage (IVH) and PHHP. We established an age-appropriate, preclinical model of PHHP with progressive macrocephaly and ventriculomegaly to test whether non-surgical neonatal treatment could modulate PHHP. We combined prenatal CAM and postnatal day 1 (P1, equivalent to 30 weeks human gestation) IVH in rats, and administered systemic erythropoietin (EPO) plus melatonin (MLT), or vehicle, from P2-P10. CAM-IVH rats developed progressive macrocephaly through P21. Macrocephaly was accompanied by ventriculomegaly at P5 (histology), and P21 (ex vivo MRI). CAM-IVH rats showed impaired performance of cliff aversion, a neonatal neurodevelopmental test. Neonatal EPO+MLT treatment prevented macrocephaly and cliff aversion impairment, and significantly reduced ventriculomegaly. EPO+MLT treatment prevented matted or missing ependymal motile cilia observed in vehicle-treated CAM-IVH rats. EPO+MLT also treatment normalized ependymal yes-associated protein (YAP) mRNA levels, and reduced ependymal GFAP-immunolabeling. Vehicle-treated CAM-IVH rats exhibited loss of microstructural integrity on diffusion tensor imaging, which was normalized in EPO+MLT-treated CAM-IVH rats. In summary, combined prenatal systemic inflammation plus early postnatal IVH caused progressive macrocephaly, ventriculomegaly and delayed development of cliff aversion reminiscent of PHHP. Neonatal systemic EPO+MLT treatment prevented multiple hallmarks of PHHP, consistent with a clinically-viable, non-surgical treatment strategy.